A concept on the dialectical methodology of empirical research: The paradigm of Focus Groups on the social and labour integration of young people - Χτούρης Σωτήρης; Ζήση Αναστασία; Ρενταρή Μάλαμα (The Greek Review of Social Research, 2016)
The present paper presents the methodology of focus groups which were applied within the context of an EC funded research program called ARISTEIA I: In4Youth as well as with the development of a dialectic qualitative methodology. This methodological approach integrates a variety of traditions of qualitative research targeting at the creation of an instrument that analyzes social data based on the interactions of the participants as well as on the dynamic dialectic of the social phenomena as these emerge. The In4Youth research project is a valuable opportunity to study the dynamics of integration or exclusion of the young people in the labor market. The method of focus group reveals the dialectics of precarity of participants with regard to their biographical trajectories within the contemporary employment or unemployment.